Gunk : a novel - Sams, Saba (Alfred A. Knopf, 2026)
"[T]he story of two women circling each other--working side by side, sleeping with the same man, inching toward friendship--until an unplanned pregnancy reveals the true nature of their connection"--Flap page 1 of dust jacket.